Paradigmatic and syntagmatic effects of information status on prosodic prominence – evidence from an interactive web-based production experiment in German - Lorenzen, Janne; Roessig, Simon; Baumann, Stefan (Frontiers in Psychology, 2024)
In this paper, we investigate how information status is encoded paradigmatically and syntagmatically via prosodic prominence in German. In addition, we consider individual variability in the production of prominence. To answer our research questions, we collected controlled yet ecologically valid speech by applying an innovative recording paradigm. Participants were asked to perform an interactive reading task in collaboration with an interlocutor remotely via video calls. Results indicate that information status is encoded paradigmatically via the F0 contour, while syntagmatic effects are subtle and depend on the acoustic parameter used. Individual speakers differ primarily in their strength of encoding and secondarily in the type of parameters employed. While the paradigmatic effects we observe are in line with previous findings, our syntagmatic findings support two contradictory ideas, a balancing effect and a radiating effect. Along with the findings at the individual level, this study thus allows for new insights regarding the redundant and relational nature of prosodic prominence.